2006
DOI: 10.1007/s00262-006-0221-z
|View full text |Cite
|
Sign up to set email alerts
|

Activation of complement C3, C5, and C9 genes in tumors treated by photodynamic therapy

Abstract: Cancer therapies, which deliver a rapidly induced massive tumor tissue injury, such as photodynamic therapy (PDT), provoke a strong host response raised for dealing with the inflicted local trauma. Activated complement system was identified as an important element of host response elicited by tumor PDT. The expression of genes encoding complement proteins C3, C5, and C9 was studied following tumor PDT mediated by photosensitizer Photofrin using mouse Lewis lung carcinoma (LLC) model. Treated tumors and the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…The lack of neutrophil infiltration in A549 tumors that were not regressing at the time of sacrifice is interesting and suggests that there is a limiting factor acting on the granulocyte lineage. This could well be due to insufficient tumor damage occurring to stimulate up-regulation of complement genes, particularly C3a, thought to be major mediators of the post-PDT neutrophil response (5). A lesser PDT response would be expected for the A549 cell line that does not express SST2r and so should not internalize the sensitizer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of neutrophil infiltration in A549 tumors that were not regressing at the time of sacrifice is interesting and suggests that there is a limiting factor acting on the granulocyte lineage. This could well be due to insufficient tumor damage occurring to stimulate up-regulation of complement genes, particularly C3a, thought to be major mediators of the post-PDT neutrophil response (5). A lesser PDT response would be expected for the A549 cell line that does not express SST2r and so should not internalize the sensitizer.…”
Section: Discussionmentioning
confidence: 99%
“…The triplet excitation energy can be effectively transferred to molecular oxygen, resulting in the generation of singlet oxygen, superoxide radical, and other active oxygen species (2,3). The singlet oxygen causes direct chemical damage to tumor and/or tumor endothelial cells (4), initiates a neutrophilic inflammatory response (5), and can stimulate both innate and specific antitumor immune responses (6 -8). Singlet-oxygen production, however, requires a sufficiently high energy of the triplet state of the sensitizer.…”
Section: Photodynamic Therapy (Pdt; Ref 1) Is a Protocol That Usesmentioning
confidence: 99%
“…Another possibility is that danger signals, such as HSP, that are induced by heat shock (Fig. 2E) up-regulate C3 expression, as shown in photodynamic therapy-treated tumors (Stott and Korbelik, 2007). An inspection of know C3 promoter sequences (human, mouse and rat) using the Match and TFSEARCH programs (available at http://www.gene-regulation.com/cgi-bin/pub/programs/match/bin/match.cgi and http://www.cbrc.jp/research/db/ TFSEARCH.html) confirmed the presence of heat shock protein binding sites (data not shown).…”
Section: Expression After a Ph Or Temperature Challengementioning
confidence: 98%
“…Cecic and Korbelik 38 showed that Photofrin-PDT induces the fixation of complement C3 protein (probably in the form of its activated fragments) and of the terminal complement membrane attack complex on the treated SCCVII cells. Stott and Korbelik 39 assessed expression of C3, C5 and C9 genes in tumours and they showed that The mechanisms of antitumour effects triggered by PDT. In the first case, PDT induces generation of reactive oxygen species (ROS) which directly can kill tumour cells by apoptosis and/or necrosis.…”
Section: Complement Activationmentioning
confidence: 99%